2018
DOI: 10.1007/s13280-018-1068-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bird community dynamics on the seasonal distribution of cultural ecosystem services

Abstract: Biodiversity-based cultural ecosystem services (CES), such as birdwatching, are strongly influenced by biotic community dynamics. However, CES models are largely static, relying on single estimates of species richness or land-use/land-cover proxies, and may be inadequate for landscape management of CES supply. Using bird survey data from the Appalachian Mountains (USA), we developed spatial-temporal models of five CES indicators (total bird species richness, and richness of migratory, infrequent, synanthrope, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…Moreover, although little explored, the seasonal variation of vegetation and animal activity may have an aesthetic value and support ecosystem services (Dronova, 2017). For instance, Graves, Pearson & Turner (2018) found that the type of cultural ecosystem services, such as birdwatching, varied spatio-temporally along an urbanization gradient, because resident and migrant species had different responses to land covers. From a point of view of urban design, it is a paradox that urban habitats that we ignore, such as vacant lots, are more related to the particular natural processes of the region in which the city is located than those places designed in a formal way with particular proportions of lawn, shrubs and trees (Hough, 1994; Kwok, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although little explored, the seasonal variation of vegetation and animal activity may have an aesthetic value and support ecosystem services (Dronova, 2017). For instance, Graves, Pearson & Turner (2018) found that the type of cultural ecosystem services, such as birdwatching, varied spatio-temporally along an urbanization gradient, because resident and migrant species had different responses to land covers. From a point of view of urban design, it is a paradox that urban habitats that we ignore, such as vacant lots, are more related to the particular natural processes of the region in which the city is located than those places designed in a formal way with particular proportions of lawn, shrubs and trees (Hough, 1994; Kwok, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although little explored, the seasonal variation of vegetation and animal activity may have an aesthetic value and support ecosystem services (Dronova, 2017). For instance, Graves et al (2018) found that the type of cultural ecosystem services, such as birdwatching, varied spatio-temporally along an urbanization gradient, because resident and migrant species had different responses to land covers. From a point of view of urban design, it is a paradox that urban habitats that we ignore, such as vacant lots, are more related to the particular natural processes of the region in which the city is located than those places designed in a formal way with particular proportions of lawn, shrubs and trees (Hough, 1994;Kwok, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Higher elevation has been correlated with low species richness (Graves et al 2019). In addition, elevation might impede the eld of view of birders, negatively affecting their birding experience.…”
Section: Variancementioning
confidence: 99%
“…We used the cultural service of bird-watching as an accessible case study from which to explore how multi-level and multi-scale interactions are related to ecosystem service production. The distributions of birds vary in geographic space, and the bene ts associated with birdwatching are well-established and globally pervasive (Graves et al 2019;Sekercioglu 2002;Whelan et al 2015). Bird-watching by its nature appears to focus on the level of individual organisms of different species.…”
Section: Introductionmentioning
confidence: 99%